2018
DOI: 10.1021/acsami.8b18451
|View full text |Cite
|
Sign up to set email alerts
|

Cell-Promoted Nanoparticle Aggregation Decreases Nanoparticle-Induced Hyperthermia under an Alternating Magnetic Field Independently of Nanoparticle Coating, Core Size, and Subcellular Localization

Abstract: Magnetic hyperthermia has a significant potential to be a new breakthrough for cancer treatment. The simple concept of nanoparticle-induced heating by the application of an alternating magnetic field has attracted much attention, as it allows the local heating of cancer cells, which are considered more susceptible to hyperthermia than healthy cells, while avoiding the side effects of traditional hyperthermia. Despite the potential of this therapeutic approach, the idea that local heating effects due to the app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 81 publications
0
42
0
Order By: Relevance
“…This effect has been attributed to Brownian mobility restriction 16,17 , or particle aggregation 18 , including also the detrimental effect of viscosity on the obtained SAR 19 . In previous studies conducted in our laboratory it has been observed that the inefficiency of the NPs to respond to AMF is due to the compaction of NPs as large aggregates with random NPs orientation in the lysosomes of Pan 02 tumor cells 20 . In contrast, several groups have recently reported cell death after MHT treatment but with disagreements about perceptible changes or not in temperature during the treatment [21][22][23] .…”
Section: Introductionmentioning
confidence: 96%
“…This effect has been attributed to Brownian mobility restriction 16,17 , or particle aggregation 18 , including also the detrimental effect of viscosity on the obtained SAR 19 . In previous studies conducted in our laboratory it has been observed that the inefficiency of the NPs to respond to AMF is due to the compaction of NPs as large aggregates with random NPs orientation in the lysosomes of Pan 02 tumor cells 20 . In contrast, several groups have recently reported cell death after MHT treatment but with disagreements about perceptible changes or not in temperature during the treatment [21][22][23] .…”
Section: Introductionmentioning
confidence: 96%
“…The heating efficiency of an ensemble of magnetic NPs depends not only on the structural and magnetic properties of NPs but also on the magnitude and frequency of the applied magnetic field, the media viscosity, and NPs concentration and aggregation state . Therefore, IO NPs displaying high heating power are currently available for MH.…”
Section: From Nanoparticles and Polymers As Building Blocks To Smart mentioning
confidence: 94%
“…Cell endocytosis, retention, and exocytosis become very important when nanoparticles are used for various types of treatments. There are reports of a reduced hyperthermia effect when nanoparticles are located in endosomes, and reports of spontaneous endosomal escape [ 113 114 ]. For the specific treatment of cisplatin-resistant nasopharyngeal carcinoma, Weng et al [ 115 ] produced SPIONs covered with cisplatin and with TAT peptide (a HIV-derived cell penetrating peptide).…”
Section: Reviewmentioning
confidence: 99%